What are my rights? - Wing, Kelisa (Racial justice in America., 2021)
Introduces readers to the Declaration of Independence, the U.S. Constitution, and the Bill of Rights. Discusses the types of rights they guarantee, the right to peacefully protest, and how one can make a difference. Includes photographs, profiles, sidebars, critical-thinking questions, activities, a glossary, and additional resources.